Expression of SOX10 in Triple-negative Breast Cancer. - Siyab Ahmad , Nadeem Zafar , Muhammad Owais Qurni , Muhammad Atif Khalil , Shabir Ahmad Orakzai , Wajahat Ahmad Khan (Journal of Islamic International Medical College, 2023)
Objective: To determine the frequency of SOX10 expression in patients with triple-negative breast cancer. Study Design:Descriptive cross-sectional study. Place and Duration of Study: Armed Forces Institute of Pathology, Combined Military Hospital, Rawalpindi, 01Dec 202 1 to 30 Sep 2022. Materials and Methods: This study was conducted on 185 patients diagnosed with triple-negative breast cancer. Patients with any size, stage and grade of breast cancer that were negative for the presence of estrogen and progesterone receptors, as well as HER2, were included. Those who were chemo-experienced, had received radiation to the breasts or had relapsed were excluded. Immunohistochemistry was performed using staining with a SOX10 antibody on patients' tissue samples for SOX10 expression, which was quantified. Data was analyzed using SPSS 26.0, and comparison was made between patients who were SOX10 positive versus those who were SOX10 negative with regards to disease characteristics. Results: The mean age of our sample population was 51.65 ± 9.81 years. SOX10 was positive in 138 (74.6%) cases, with patchy positivity seen in 55 (29.7%) samples, while focal and diffuse involvement was seen in 67 (36.2%) and 16 (8.7%) cases respectively. Higher SOX10 positivity was seen with advancing age, (p=0.014), larger tumour size, (p<0.001), and higher tumour grade, (p=0.003). Diffuse and focal involvement were associated with higher grade tumours, (p<0.001), while degree of SOX10 expression did not appear to have a statistically significant association with disease stage, (p=0.618). Conclusion: SOX10 is a useful marker that can be frequently detected in triple-negative breast cancer and is associated with more aggressive disease characteristics at presentation.